RELATIONSHIP OF PERIURETHRAL FIBROTIC IN BPH PATIENT WITH LUTS AND URINARY RETENTION - Zamroni, Zamroni; Hardjowijoto, Sunaryo; Soetojo, Soetojo (Indonesian Urological Association, 2017)
Objective: Analyzing the differences between collagen thicknesses in periurethral region from transurethral resection of the prostate (TURP) specimens of Benign Prostate Hyperplasia (BPH) patients with lower urinary tract symptoms (LUTS) and of those with urinary retention. Material & methods: This was an observation analytic study on 30 patients who underwent TURP. Patients who met the inclusion criteria were divided into 2 groups: BPH patients with LUTS and those with urinary retention. Each group consisted of 15 people. The first TURP specimen of proximal verumontanum resection were examined in anatomic pathology using mass on strichrome staining as an examination of periurethral collagen thickness. Collagen will be stained as blue. Periurethral collagen thickness was measured from the basal membrane of transitional epithelium to fibromuscle tissue. Data were then statistically analyzed using independent t-test. Results: The average patient age was 66 ± 7 years old and there was no significant difference between age and periurethral collagen thickness with p=0.175 (p>0.05). The mean prostate volume was 47.19 ± 13.2 ml and there was no significant difference between prostate volume and periurethral collagen thickness with p=0.148 (p>0.05). Average periurethral collagen thickness in BPH patients with urinary retention was 146.67 ± 39.80 micrometers and while in those with LUTS was 205.33 ± 85.6 micrometers. There were no significant differences between periurethral collagen thickness and the occurrence urinary retention with retention of urine with p=0.063 (p>0.05). Conclusion: There were no significant differences between periurethral collagen thickness patients in BPH patients with LUTS and in those with urinary retention. This suggests that periurethral collagen thickness is not associated with the occurrence of urinary retention or LUTS in BPH patients.